A green marine self-cleaning antifouling coating and preparation method thereof

By mixing ZnxFeyTizCaNbOc photocatalyst with aqueous resin, green ocean self-cleaning antifouling coating was prepared, which solved the problem of using toxic chemicals and poor environmental adaptability in existing coatings, and achieved efficient and safe self-cleaning antifouling effect.

CN118988381BActive Publication Date: 2025-02-14YANTAI INST OF COASTAL ZONE RES CHINESE ACAD OF SCI
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411479411.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-02-14
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

Existing marine antifouling coatings have problems with the use of toxic chemicals, high cost, limited validity period and poor results in some environments, and modification methods of titanium dioxide may lead to marine environmental pollution.

Method used

ZnxFeyTizCaNbOc was used as the photocatalyst, and visible photocatalyst was prepared by sol-gel method, and mixed with aqueous resin to prepare green ocean self-cleaning antifouling coating. The photocatalyst can decompose organic matter and bacteria under sunlight, achieving self-cleaning function.

Benefits of technology

It improves the self-cleaning ability of antifouling coatings, reduces the electron hole recombination rate, significantly improves the ability to photocatalyze the degradation of organic matter and removes microbial adhesion, and has safe materials and low production costs, reducing pollution to the marine environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118988381B_ABST
    Figure CN118988381B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of marine antifouling coatings, and specifically relates to a green marine self-cleaning antifouling coating and a preparation method thereof. x Fe y Ti z C a N b O c , its crystal form is rutile, and the lattice spacing is 3.63Å. The catalyst is added to the coating as a green marine self-cleaning antifouling coating. The active free radicals generated by the green marine self-cleaning antifouling coating under sunlight can decompose organic matter and bacteria attached to the surface of the coating into carbon dioxide and water, and form a super hydrophilic film on the surface, which can prevent the attachment of fouling organisms. The green marine self-cleaning antifouling coating of the present invention has the functions of maintenance-free and self-cleaning. The coating is green and environmentally friendly, simple to prepare and has a wide range of uses, and can effectively improve the performance and service life of marine facilities.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of marine anti-biological fouling coatings, and in particular relates to a green marine self-cleaning anti-fouling coating and a preparation method thereof. Background Art

[0002] When an object is immersed in seawater, its surface will immediately undergo physical changes, and a layer of conditional film composed of organic molecules will be adsorbed on the surface. These organic molecules include proteins, polysaccharides, lipids, etc. They will quickly adsorb on the surface of the object, providing conditions for the subsequent attachment of organisms; after the conditional film is formed, microorganisms (such as bacteria, fungi, algae) begin to attach to the surface of the object to grow and reproduce, forming a microbial biofilm (Biofilm). These biofilms can further attract other larger fouling organisms to attach; over time, larger organisms such as algae, seaweed, sponges and other fouling organisms will attach to their surface, increasing the thickness of the fouling layer. These organisms not only increase the weight of the object by attaching, but may also affect the surface of the object through the substances they secrete, further aggravating the fouling; eventually, some large marine fouling organisms such as barnacles and mussels will adsorb on the surface of the object. If they attach to the surface of artificial marine facilities, they will increase the resistance of the ship's navigation, increase fuel consumption, and affect the performance and service life of underwater sensors and other detection equipment.

[0003] Marine antifouling coatings are coating materials specially designed to reduce or prevent the attachment of marine organisms to the surface of artificial facilities such as underwater sensors, ships, offshore platforms, and submarine pipelines. It prevents biofouling through physical, chemical or biological means, thereby protecting the performance of the equipment and extending its service life.

[0004] Although current marine antifouling coatings can effectively reduce biofouling to a certain extent and for a certain period of time, they still have many disadvantages. Some coatings with better antifouling properties often contain toxic chemicals, which limit their use due to their environmental damage. In addition, the coatings are expensive, have a limited shelf life, and are not effective in certain special environments. Over time, the coatings may deteriorate and fail, increasing the difficulty and cost of maintenance.

[0005] At present, self-healing coatings can use TiO2 to generate holes, electron pairs and highly active hydroxyl radicals (·OH) with redox ability through the drive of light. ·OH can decompose or kill organic matter or bacteria attached to the coating surface, and the hole-electron pairs induce water molecules to form a super-hydrophilic film on the coating surface, which can prevent the adsorption of fouling organisms. However, due to the wide band gap of TiO2, it can only be activated by ultraviolet light, which accounts for about 4% of the solar spectrum. Its practical application is limited by a relatively wide band gap, which limits its sensitivity under visible light / sunlight. During illumination, the photogenerated electrons-holes on titanium dioxide are easily recombined, which has an adverse effect on its photocatalytic performance. At present, most of the modification methods of titanium dioxide are doped with heavy metals, which will harm the marine environment and cause pollution. Summary of the invention

[0006] In view of the deficiencies in the prior art, the present invention provides a green marine self-cleaning antifouling coating and a preparation method thereof.

[0007] To achieve the above object, the technical solution adopted by the present invention is:

[0008] A photocatalyst, the photocatalyst is Zn x Fe y Ti z C a N b O c , its crystal form is anatase with a lattice spacing of 3.63 Å.

[0009] The content of each element of the photocatalyst is x: 2-5wt%, y: 1-4wt%, z: 25-30wt%, a: 2-5wt%, b: 5-8wt%, and c: 55-60wt% respectively in terms of mass percentage.

[0010] The method for preparing the photocatalyst comprises slowly pouring tetrabutyl titanate into anhydrous ethanol and stirring to obtain solution A;

[0011] Anhydrous ethanol, acetylacetone and water are mixed in a certain proportion and stirred vigorously to obtain solution B;

[0012] Add ferric chloride hexahydrate, urea and anhydrous zinc chloride to the solution B in sequence and mix evenly, then drop solution A thereinto, and heat the solution in a water bath to obtain a yellow gel C after the dropwise addition;

[0013] The yellow gel C is dried to obtain pale yellow crystals D, which are ground to obtain pale yellow powder; and the pale yellow powder obtained by calcination is the photocatalyst Zn x Fe y Ti z C a N b Oc .

[0014] Zn (2-5) Fe (1-4) Ti (25-30) C (2-5) N (5-8) O (55-60) Preparation of photocatalyst: the dripping rate of the solution A into the solution B is controlled at 3-5 ml / min; the temperature of the water bath is 50-60°C and the water bath time is 1-2 h; after the yellow gel C is formed, it is aged for 2-5 days; the oven temperature is 100-120°C and the heating time is 20-24 h; the muffle furnace calcination temperature is 500-600°C and the calcination time is 2-3 h.

[0015] Anhydrous ethanol, acetylacetone and water are mixed in a volume ratio of 60-70:1-2:15-20.

[0016] The volume ratio of ferric chloride hexahydrate, urea, anhydrous zinc chloride and water in solution B is 23-25:5-6:29-30:10-15.

[0017] The invention discloses an application of a photocatalyst in preparing a green marine self-cleaning antifouling coating.

[0018] A green marine self-cleaning antifouling paint contains the photocatalyst in an amount of 1.0-1.5wt% of the paint mass.

[0019] The green ocean self-cleaning antifouling coating has a water-based resin content of 95.0-97.0wt%, a dispersant content of 0.8-1.0wt%, a leveling agent content of 0.8-1.0wt%, a defoamer content of 0.8-1.0wt%, a photocatalyst content of 1.0-1.5wt%, and the balance is water.

[0020] The pH value of the water-based resin is 7.0±0.5, and the viscosity is 100.0-1000.0 cps.

[0021] The invention discloses an application of a green marine self-cleaning antifouling coating as an antifouling coating for marine antifouling equipment.

[0022] Furthermore, the green ocean self-cleaning antifouling coating can decompose organic matter attached to the surface of the coating into carbon dioxide and water under sunlight, remove microorganisms attached to the surface of the coating, and has the function of maintenance-free self-cleaning.

[0023] The advantages of the present invention are:

[0024] 1. The present invention uses the addition of transition metal Fe and Zn elements and non-metallic N and C elements to change the chemical properties of titanium dioxide, so that it can decompose organic matter and remove microorganisms attached to the surface under the irradiation of sunlight, which not only solves the problem of heavy metal pollution of the marine environment, but also further increases the self-cleaning ability of antifouling coatings (increasing the light response range of TiO2 and slowing down the electron-hole coincidence rate). (2-5) Fe (1-4) Ti (25-30) C (2-5) N (5-8) O (55-60) It can decompose organic matter and bacteria attached to the surface of objects into non-toxic carbon dioxide and water, and remove them under the flushing of water flow, so as to achieve self-cleaning of the surface of objects. And when mixed with water-based resin, because it contains carboxyl, hydroxyl and other groups, other reactive groups can be introduced under appropriate conditions to make the resin cross-linked and solidified into a film. Furthermore, the present invention uses water-based resin as the main film-forming substance and Zn x Fe y Ti z C a N b O c Self-cleaning coatings are prepared for antifouling agents and surface coated on equipment to obtain visible light / sunlight-driven catalytic, maintenance-free, self-cleaning coatings for use in preventing marine biofouling of aquatic equipment.

[0025] 2. The catalyst synthesized by the present invention greatly reduces the recombination rate of electron holes, significantly improves the ability of antifouling coatings to photocatalytically degrade organic matter and remove microbial attachment, and the synthetic materials are simple and inexpensive, and the synthetic process is simple, which effectively reduces the production cost of the coating and reduces the production steps. The obtained coating adopts a non-toxic or low-toxic material formula, which reduces the pollution to the marine environment compared to traditional toxic antifouling coatings and meets environmental protection requirements.

[0026] 3. The composite coating of the present invention can be applied to a variety of marine facilities, including underwater sensors, ships, submarine pipelines, marine platforms, etc. The present invention can play a huge role in preventing marine biofouling of various underwater facilities. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Characterization diagram of the visible light catalyst obtained in Example 1 of the present invention, wherein (a) is an X-ray diffraction diagram (XRD) and (b) is a high-resolution transmission electron microscopy diagram (HRTEM).

[0028] Figure 2 These are the visible light catalyst characterization images obtained in Example 1 of the present invention, where (a) is the ultraviolet diffuse reflectance image (UV-VIS) and (b) is the electronic impedance spectroscopy (EIS).

[0029] Figure 3 Characterization diagram of the visible light catalyst obtained in Example 1 of the present invention, wherein (a) is the Mott-Schottky curve (MS), and (b) is the photocurrent density curve (It).

[0030] Figure 4 The photocatalytic degradation effect diagram of organic matter provided in Example 1 of the present invention (visible light catalyst degradation of rhodamine), wherein (a) is Zn3Fe2Ti 30 C3N6O 56 Photocatalytic degradation effect diagram, (b) is the photocatalytic degradation effect diagram of TiO2, (c) is the photocatalytic degradation effect diagram of Fe-TiO2, and (d) is the photocatalytic degradation effect diagram of Fe / Zn-TiO2.

[0031] Figure 5 This is a diagram showing the effect of the photocatalyst provided in Example 1 of the present invention on photodegrading organic substances methyl orange and rhodamine b under sunlight.

[0032] Figure 6 The visible light catalyst sterilization effect diagram provided in Example 2 of the present invention, wherein (a) is a colony growth effect diagram without adding catalyst and bacteria, (b) is a colony growth effect diagram without adding catalyst and bacteria, (c) is a colony growth effect diagram with the addition of TiO2 catalyst and bacteria, (d) is a colony growth effect diagram with the addition of Fe-TiO2 catalyst and bacteria, (e) is a colony growth effect diagram with the addition of Fe / Zn-TiO2 catalyst and bacteria, and (f) is a colony growth effect diagram with the addition of Zn3Fe2Ti 30 C3N6O 56 The effect of adding bacteria to the catalyst is shown in the colony growth effect diagram.

[0033] Figure 7 This is a mechanism diagram of the green marine self-cleaning antifouling coating (with maintenance-free, self-cleaning, and organic matter decomposition and sterilization functions) provided in Example 3 of the present invention.

[0034] Figure 8 The physical property characterization diagram of the green marine self-cleaning antifouling coating provided in Example 3 of the present invention, (a) is thermogravimetric analysis; (b) is particle size analysis; (c) is adhesion; and (d) is contact angle.

[0035] Fig. 9 The green marine self-cleaning antifouling coating provided in Example 4 of the present invention is used in marine monitoring equipment (Ca 2+ -ISE) application effect diagram. (a) is the potential response diagram of blank electrode, waterborne polyurethane modified electrode and self-cleaning coating modified electrode over time, Ca 2+ The concentration is 10 -5 -10 -1M; (b) is the potential response diagram of the electrode modified with commercial coating over time, Ca 2+ The concentration is 10 -3 -10 -1 M; (c) is the real-time potential response diagram of the blank electrode, the electrode modified with waterborne polyurethane and the electrode modified with self-cleaning coating, Ca 2+ Concentration from 10 -3 Increase to 10 -2 M; (d) is the real-time potential response diagram of the electrode modified with commercial coating, Ca 2+ Concentration from 10 -3 Increase to 10 -2 M; (e) is the statistical graph of the electrode response slope of the blank electrode, the electrode modified with waterborne polyurethane, the electrode modified with self-cleaning coating, and the electrode modified with commercial coating over time, Ca 2+ The concentration is 10 -5 -10 -1 M; (f) is the response time statistics of blank electrode, electrode modified with waterborne polyurethane, electrode modified with self-cleaning coating and electrode modified with commercial coating, Ca 2+ Concentration from 10 -3 Increase to 10 -2 M.

[0036] Fig.10 The green marine self-cleaning antifouling coating modified Ca provided in Example 4 of the present invention 2+ -Characterization of the antibacterial ability of ISE surface (laser confocal CLSM).

[0037] Fig.11 The green self-cleaning antifouling coating modified Ca provided in Example 4 of the present invention 2+ -ISE stability analysis diagram, where (a) is the Nernst slope of the electrode after being immersed in seawater for different time periods; (b) is the change of the electrode slope after being immersed in seawater for different time periods.

[0038] Fig.12 This is a comparison chart of the green marine self-cleaning antifouling coating provided in Example 5 of the present invention and a blank after being immersed in seawater for 60 days.

[0039] Fig.13 This is a graph showing the weight change of the substrate of the green marine self-cleaning antifouling coating provided in Example 5 of the present invention after being immersed in seawater for 60 days. DETAILED DESCRIPTION

[0040] The present invention is further described below in conjunction with examples. It should be noted that the specific implementation methods described herein are only for illustrating and explaining the present invention and are not intended to limit the present invention.

[0041] The present invention adopts the sol-gel method to prepare the visible light catalyst, and mixes the catalyst with water-based resin and other water-based additives in proportion to prepare the green marine self-cleaning antifouling coating, thereby reducing the loss of marine facilities in seawater due to marine fouling and extending the service life of the marine facilities. Example 1

[0042] a. Synthesis of Fe-TiO2 catalyst: 10.0 ml of tetrabutyl titanate was slowly poured into 25.0 ml of anhydrous ethanol, and stirred for 10 min to obtain solution A; 10.0 ml of deionized water, 35.0 ml of anhydrous ethanol, and 0.5 ml of acetylacetone were measured and mixed and stirred to obtain solution B; 0.1 mol / L ferric chloride hexahydrate was prepared, 23.5 ml of 0.1 mol / L ferric chloride hexahydrate solution was drawn and poured into solution B, and stirred at room temperature for 10 min until uniform; after stirring, solution A was poured into solution B at a pouring speed of about 5.0 ml / min, and aged for 2 days to obtain a yellow gel, which was dried in an oven at 100 °C to obtain yellow crystals, which were ground and calcined to obtain a light yellow powder, which was the Fe-TiO2 visible light catalyst (as a control).

[0043] b. Synthesis of Fe / Zn-TiO2 catalyst: 10.0 ml of tetrabutyl titanate was slowly poured into 25.0 ml of anhydrous ethanol and stirred for 10 min to obtain solution A; 10.0 ml of deionized water, 35.0 ml of anhydrous ethanol and 0.5 ml of acetylacetone were measured and mixed and stirred to obtain solution B; 0.1 mol / L ferric chloride hexahydrate and zinc chloride hexahydrate solutions were prepared, 23.5 ml of 0.1 mol / L ferric chloride hexahydrate solution and 29.4 ml of 0.1 mol / L zinc chloride hexahydrate were drawn into solution B and stirred at room temperature for 10 min until uniform; after stirring, solution A was poured into solution B at a pouring speed of about 5.0 ml / min, and aged for 2 days to obtain a yellow gel, which was dried in an oven at 100°C to obtain yellow crystals, which were ground and calcined to obtain a light yellow powder, namely the Fe / Zn-TiO2 visible light photocatalyst (as a control).

[0044] c.Zn x Fe y Ti z C a N b O cPhotocatalyst synthesis: 10.0 ml of tetrabutyl titanate was slowly poured into 25.0 ml of anhydrous ethanol and stirred for 10 min to obtain solution A; 10.0 ml of deionized water, 35.0 ml of anhydrous ethanol, and 0.5 ml of acetylacetone were measured and mixed and stirred to obtain solution B; 0.1 mol / L ferric chloride hexahydrate and zinc chloride hexahydrate solutions were prepared, 23.5 ml of 0.1 mol / L ferric chloride hexahydrate solution and 29.4 ml of 0.1 mol / L zinc chloride hexahydrate were drawn into solution B and stirred for 10 min; 150.2 mg of urea was weighed and slowly poured into solution B, and stirred at room temperature for 10 min until uniform; after stirring, solution A was poured into the above solution B at a pouring speed of about 5.0 ml / min, and aged for 2 days to obtain a yellow gel, which was dried in an oven at 100°C to obtain yellow crystals, which were ground and calcined to obtain a light yellow powder, namely Zn x Fe y Ti z C a N b O c Visible light catalyst.

[0045] d. Characterization of the photocatalyst performance obtained above: In order to analyze the composite catalyst Zn3Fe2Ti 30 C3N6O 56 The catalyst was characterized by X-ray diffraction. Figure 1 As shown in (a), it can be seen from the XRD spectrum that Zn3Fe2Ti 30 C3N6O 56 The catalyst has characteristic diffraction peaks of TiO2 (2θ is 25.3°, 37.8°, 48.0°, 53.9°, 62.7°), proving that Zn3Fe2Ti 30 C3N6O 56 The crystal form of the catalyst is anatase, indicating that the photocatalyst has good chemical stability and excellent photocatalytic performance. Figure 1 (b) Transmission electron microscopy (TEM) and Fourier transform high-resolution transmission electron microscopy (HRTEM) show the nanoparticle appearance of the catalyst and the (101) plane of the anatase crystal with a planar lattice spacing of 3.63 Å. The photoresponse of the photocatalyst was studied by UV-vis absorption spectroscopy, as shown in Figure 2. Figure 2 As shown in (a), the light absorption of TiO2 is mainly concentrated in the ultraviolet region, but is weak in the visible region. After doping modification, the absorption intensity in the visible region is enhanced, and the absorption spectrum is red-shifted. According to the Kubelka-Munk formula, Zn3Fe2Ti 30 C3N6O 56The bandgap widths (Eg) of and TiO2 are 2.72 eV and 3.18 eV respectively. It can be seen that doping with N and C elements will affect the 2p orbital of oxygen, and adding Fe and Zn to the TiO2 structure will cause lattice distortion. Figure 2 (b) and Figure 3 (a) shows Zn3Fe2Ti 30 C3N6O 56 The electronic impedance and Mott-Schottky curves of TiO2 are shown in Figure 2. The electronic impedance diagram consists of a semicircle in the high-frequency region and a straight line in the low-frequency region. The diameter of the semicircle in the high-frequency region reflects the charge transfer resistance. The results show that compared with TiO2, Zn3Fe2Ti 30 C3N6O 56 The smaller semicircle radius means that the arc resistance is reduced, thereby enhancing the ability of photoinduced carrier migration. These results show that Zn3Fe2Ti 30 C3N6O 56 The Mott Schottky curve (MS) shows that Zn3Fe2Ti 30 C3N6O 56 The catalyst is a composite semiconductor. Figure 3 (b) shows the photocurrent density curve of the photocatalyst. TiO2 shows a weak photocurrent response under natural light, while the doped and modified catalyst Zn3Fe2Ti 30 C3N6O 56 The photocurrent of is significantly higher, which verifies the synergistic effect of co-doping with transition metal elements Fe and Zn and non-metallic elements N and C on improving the photocatalytic performance.

[0046] In summary, Zn3Fe2Ti 30 C3N6O 56 The catalyst generates more electron-hole pairs through sunlight irradiation, the migration capacity of electron-hole pairs is enhanced, and the recombination rate is slowed down. These effects help to synergistically enhance the efficiency of pollutant degradation.

[0047] e. Verification of the synthesis of Zn3Fe2Ti 30 C3N6O 56 Anti-organic pollution performance of the catalyst: Rhodamine b (RHb 10 mg / L) was used to verify the photocatalytic effect, and the degradation of Rhodamine b was characterized by UV-visible spectrophotometer. The results are as follows: Figure 4 shown.

[0048] The experimental steps are as follows: First, prepare a 10 mg / L rhodamine b solution, weigh 50 mL and pour it into a beaker. Then add 50 mg of the above-obtained Zn3Fe2Ti 30 C3N6O 56Photocatalyst, and after ultrasonic treatment for 5 minutes, the solution was placed in a dark reaction system and stirred for 30 minutes to ensure that the reaction reached equilibrium. After equilibrium, 1 mL of solution was taken from the beaker and placed in a 1.5 mL centrifuge tube, which was recorded as the 0-minute sample. Subsequently, the sample was exposed to a light source with a wavelength greater than 470 nm (Agilent Technologies (China) Co., Ltd.), and samples were taken in sequence at illumination times of 10 minutes, 20 minutes, 30 minutes, 60 minutes, 90 minutes, and 120 minutes. After each sampling, the sample was centrifuged at 5000 r / min and then tested using a UV-visible spectrophotometer. Since rhodamine b has a maximum absorption wavelength at 554 nm, but intermediate products are generated during the degradation process, the wavelength of the maximum absorption peak was selected as a reference indicator for the degradation rate in the experiment. The final experimental results showed that the degradation rate of rhodamine b reached 91.89% in 120 minutes. Using the same method, the above photocatalyst was replaced with commercial anatase TiO2 (Xianfeng Nano), and the degradation rate of rhodamine b in 120 minutes was only 19.76%. In addition, using the synthetic control Fe-TiO2 and Fe / Zn-TiO2 catalysts, according to the same experimental method, the degradation rates of rhodamine b in 120 minutes were 34.67% (Fe-TiO2) and 52.87% (Fe / Zn-TiO2), respectively. This experimental result fully proves that the Zn3Fe2Ti 30 C3N6O 56 The catalyst has excellent photocatalytic ability.

[0049] f. Verification of Zn3Fe2Ti 30 C3N6O 56 Catalyst degradation of organic matter under sunlight: Replace the light source with sunlight and keep other experimental steps unchanged. Figure 5 After 6 hours of sunlight exposure, Zn3Fe2Ti 30 C3N6O 56 The catalyst successfully degraded rhodamine b (RHb) and methyl orange (MO) into a colorless and transparent solution. However, commercial anatase titanium dioxide (Xianfeng Nano) showed almost no change after 6 hours of sunlight exposure. This is because unmodified TiO2 needs ultraviolet light to produce active free radicals, and ultraviolet light only accounts for 4% of sunlight. Therefore, the photocatalytic degradation rate is extremely slow. This experimental result fully proves the excellent catalytic performance of the catalyst under natural light. Example 2

[0050] Verification of Zn3Fe2Ti 30 C3N6O 56 Bactericidal performance of catalysts: Characterization of Zn3Fe2Ti by plate colony count 30 C3N6O56 The antibacterial properties of photocatalysts. The operation steps are as follows:

[0051] Prepare Luria-Bertani (LB) liquid medium (6 g dry powder dissolved in 200 mL ultrapure water), stir evenly until fully dissolved, and after high-pressure sterilization, cool the liquid medium to room temperature for use. Inoculate Pseudomonas aeruginosa strains into the sterilized LB medium and culture overnight in a constant temperature incubator at 37 °C with a shaking speed of 120 rpm min -1 . Inoculate 1 mL of the above cultured bacterial solution into 9 mL of sterile LB medium and culture in a constant temperature incubator at 37°C for 2 h. Take out the bacterial solution and place it in a centrifuge tube for centrifugation for 5 min (5000 rpm·min -1 ), discard the separated medium. Use 0.9% NaCl solution to disperse the bacterial plaques obtained by centrifugation, centrifuge for 5 min, and repeat three times to remove the LB medium in the bacterial plaques.

[0052] The cleaned plaque was evenly dispersed with 0.9% NaCl solution (pH=8.0), and the dilution ratio of the bacterial solution was adjusted using a UV-visible spectrophotometer to adjust the bacterial solution concentration to about 10 8 or 10 9 CFU·mL -1 (Absorbance at 600 nm is 0.15).

[0053] The bacteria obtained above were subjected to 4 Dilution, spread the diluted bacterial solution on solid LB culture medium, add 1 mg of the photocatalyst obtained in Example 1a, b, c for every 1 ml of bacterial solution, mix well and spread on solid LB culture medium, incubate for 12 h under light (>470 nm), and at the same time, use no catalyst and commercial TiO2 (Xianfeng Nano) as blank controls.

[0054] The experimental results are as follows Figure 6 As shown in the figure, under visible light irradiation, a large amount of bacterial growth was observed on the plate without adding catalyst. The bactericidal effects of the three photocatalysts TiO2, Fe-TiO2 and Zn / Fe-TiO2 were relatively limited, and none of them achieved the optimal sterilization efficiency. 30 C3N6O 56 The photocatalyst showed a significantly superior bactericidal effect, with a sterilization efficiency of 100%. This result shows that Zn3Fe2Ti 30 C3N6O 56 It has more efficient photocatalytic sterilization performance under visible light irradiation, which is better than conventional TiO2-based catalysts. Example 3

[0055] a. Synthesis of green ocean self-cleaning antifouling coating: weigh 20 ml of waterborne polyurethane; 200 μl of waterborne cationic dispersant; 200 μl of waterborne organosilicon-modified leveling agent; 200 μl of waterborne organosilicon-modified defoamer and 200 mg of Zn3Fe2Ti 30 C3N6O 56 Composite photocatalyst, the above components were heated at 2000 r·min -1 The mixture was dispersed under the conditions of 400 μm for 20 min, and then ultrasonically dispersed for 30 min to obtain a uniform aqueous resin dispersion system. After stirring for 24 hours, a visible light catalytic antifouling coating was obtained.

[0056] b. The mechanism of action of Green Ocean self-cleaning antifouling coating is as follows Figure 7 As shown: Under sunlight, the green ocean self-cleaning antifouling coating will produce active free radicals, decompose the organic matter attached to its surface into carbon dioxide and water, remove bacteria and other microorganisms adsorbed on the surface of the coating, and achieve self-cleaning under the flushing of water flow.

[0057] c. Characterization of green antifouling coating performance: The thermodynamic properties of green marine self-cleaning antifouling coating were studied. Figure 8 As shown in (a), the green ocean self-cleaning antifouling coating has ideal thermal stability and good film-forming properties at ambient temperature. The average particle size distribution of the latex particles of the green ocean self-cleaning antifouling coating was characterized. Figure 8 As shown in (b), the average particle size of the latex particles is 148 nm, and the distribution is uniform. In order to expand the application range of antifouling coatings, the adhesion grade of the coating (where grade 5 represents the best adhesion and grade 0 represents the worst) and the water contact angle are calculated according to the American Iron and Steel Institute (ASTM) standard. Figure 8 From (c), we can see that the adhesion of the coating on PE is slightly lower, which is level 4. The adhesion on metals Al, Cu, Fe, titanium alloy, 304 stainless steel and pine wood is the best, which is level 5. Figure 8 As can be seen in (d), the coating significantly reduces the water contact angle on the substrate surface, which is beneficial to improving the hydrophilicity of the substrate and improving the anti-adhesion ability of the substrate. Example 4

[0058] The green marine self-cleaning antifouling coating synthesized by the present invention is applied to underwater sensors of marine monitoring equipment (Ca 2+ -ISE).

[0059] a. Synthesis of green marine self-cleaning antifouling coating: The synthesis steps are the same as in Example 3a.

[0060] b. Preparation of polymer membrane calcium ion selective electrode: A mixture of 360 mg of PVC particles, o-nitrophenyl octyl ether, calcium ion carrier ETH129 and sodium tetrakis(3,5-di(trifluoromethyl)phenyl)borate, in which the contents of each component were 31.8 wt% PVC particles, 63.7 wt% o-nitrophenyl octyl ether, 2.3 wt% calcium ion carrier and 2.2 wt% sodium tetrakis(3,5-di(trifluoromethyl)phenyl)borate, was transferred into 3.6 mL of tetrahydrofuran solution, and ultrasonicated and stirred for 2 hours to make it evenly dispersed. The membrane solution was poured into a glass ring (3.6 cm in diameter) fixed on a glass plate and evaporated naturally overnight. The pipette was inserted into the PVC tube, and then a perforated membrane was glued to the PVC tube with THF. The electrode was heated at 10 °C before use. -3 Activated with M CaCl2 for 12 h.

[0061] c. Preparation of calcium ion selective electrode modified with green ocean self-cleaning antifouling coating: 20.0 μL of the coating prepared in step a was dripped onto the surface of the calcium ion selective electrode obtained in step b (20.0 μL of water-based polyurethane was dripped onto the surface of the electrode as a reference), and after drying, a green ocean self-cleaning antifouling electrode and a water-based polyurethane electrode (Ca 2+ -ISE). The potential (EMF) was measured at room temperature using an electrochemical workstation (CHI-760D, Shanghai Chenhua Instrument Co., Ltd., China) with an Ag / AgCl electrode as the reference electrode. Before the potential measurement, the membrane electrode (Ca 2+ -ISE) placed at 10 -3 M CaCl2 solution overnight.

[0062] d. Preparation of a calcium ion selective electrode modified with commercial marine antifouling coating: The green self-cleaning antifouling coating in step c was replaced with a commercial marine antifouling coating (Anhui Kailin New Materials Co., Ltd.), and the remaining steps remained unchanged to obtain a commercial marine antifouling coating electrode (Ca 2+ -ISE).

[0063] e. Performance test: A detailed study of the Ca content of waterborne polyurethane, green marine self-cleaning antifouling coating and commercial antifouling coating before and after modification in an environment close to seawater (i.e., 0.5 M NaCl, pH=8.0) 2+ -Electrochemical properties of ISE, such as Fig. 9 The Nernst slope of the electrode modified with waterborne polyurethane obtained in step c is 26.40 ± 0.25 mV·dec -1 , the response time is 1.91 s; the Nernst slope of the electrode modified with the green ocean self-cleaning antifouling coating obtained in step c is 27.38 ± 0.30 mV·dec -1, the response time is 4.52 s; the Nernst slope of the electrode modified with the commercial antifouling coating obtained in step d is 12.7 ± 0.12 mV·dec -1 The response time was 16.7 s, while the Nernst slope of the unmodified control electrode was 26.97 ± 0.03 mV·dec -1 , the response time is 0.71 s; it can be seen that compared with the control electrode, the green ocean self-cleaning antifouling coating provided by the present invention has little effect on the linear range and Nernst slope of the electrode, and does not affect the performance of the electrode. However, the commercial coating has a great influence on the electrochemical properties of the electrode (large impedance, no Nernst response), and may even make it unusable.

[0064] f. Study on the Ca after modification of green ocean self-cleaning antifouling coating 2+ -ISE bactericidal ability: Take fresh Pseudomonas aeruginosa liquid and centrifuge it at 5000 rpm for 5 min, wash it with saline for 3 times, and finally dilute the bacteria with saline. 2+ -ISE polymer sensitive membrane and Ca-modified green marine self-cleaning antifouling coating 2+ -ISE polymer sensitive membrane was immersed in the bacterial solution for 2 hours and then irradiated under visible light for 5 minutes. The polymer sensitive membrane was taken out and rinsed with deionized water. The bacteria were stained with a certain concentration of SYTO 9 and PI, and then characterized by laser confocal scanning microscopy. The results are as follows: Fig.10 Shown: Blank Ca 2+ A large number of bacteria are attached to the surface of the ISE polymer sensitive membrane, which modifies the antifouling Ca 2+ -The number of bacteria attached to the surface of the ISE polymer sensitive membrane is relatively small, proving that the Green Ocean self-cleaning antifouling coating has excellent antifouling ability.

[0065] g. Study on the antifouling performance of electrodes: In order to explore the antifouling ability of green marine self-cleaning antifouling coatings in real seawater environments, a detailed investigation was conducted on the Zn3Fe2Ti 30 C3N6O 56 Electrochemical performance of electrodes before and after modification with green ocean self-cleaning antifouling coating after immersion in real seawater environment.

[0066] Immerse the antifouling electrode prepared in step c and the blank electrode in seawater (50 cm from the sea surface) and observe the response performance of the electrode at regular intervals (after the electrode is arranged outdoors, use a handheld PXBJ-287L portable ion meter to test the open circuit potential of the calcium ion electrode on-site under zero current conditions and record the data. The concentration range is 10 -3 ~10 -1 mol·L -1 ). The results are as follows Fig.11As shown in the figure, it can be seen that after the blank electrode is immersed in the real seawater environment, the Nernst slope changes from 28.13± 0.69 mV·dec -1 Down to 4.08 ± 0.57 mV·dec -1 However, after the modified electrode was immersed in the real seawater environment, the Nernst slope changed slightly, from 28.86 ± 0.41 mV·dec -1 Down to 24.24 ± 1.37 mV·dec -1 The above experimental results show that the coating does not significantly affect the response performance of the electrode, has good anti-fouling ability, and significantly improves the performance and service life of the potentiometric sensor. Example 5

[0067] The green marine self-cleaning antifouling coating synthesized by the invention is applied to a substrate.

[0068] a. Synthesis of green marine self-cleaning antifouling coating as in Example 3a.

[0069] b. Customize a metal iron plate of 15 cm long × 10 cm wide × 4 mm high, an alloy 304 stainless steel plate, and a wooden pine board, and punch holes in their four corners.

[0070] c. Soak the substrate in water for 30 minutes to remove the surface attachments, and then polish it with sandpaper. Use a spray gun to spray the green ocean self-cleaning antifouling coating synthesized in step a on the customized substrate in step b, and spray it three times to form a coating with a thickness of about 150 μm on the substrate. After spraying, place it in a cool place to dry.

[0071] d. Immerse the treated substrate in the seawater of Muping District, Yantai City, with the board about 20 cm from the sea surface, and immerse for 60 days. Fig.12 As shown. After 60 days of seawater immersion, the surfaces of 304 stainless steel plates and pine wood substrates that were not coated with green ocean self-cleaning antifouling coatings were covered with a large number of algae and other fouling organisms; the iron plate was corroded in seawater, and ferric oxide was generated on the surface and fell off, resulting in obvious reddish-brown rust on the surface. However, only a small amount of fouling appeared on the surface of the substrate coated with green ocean self-cleaning antifouling coatings. Since the resin used is a green and environmentally friendly water-based resin, the coating shows good hydrophilicity. Although bubbles will appear on the surface of the plate after immersion for a period of time, the coating does not fall off and does not affect its performance.

[0072] e. After the experiment, the plates were taken out, dried and weighed. The results showed that the weight of the 304 stainless steel substrate without antifouling coating increased by 3.7 grams, the pine wood substrate increased by 2.6 grams, and the iron plate decreased by 2.4 grams due to corrosion and shedding (i.e., the iron was oxidized in seawater to form ferric oxide and then fell off). In contrast, the weight of the 304 stainless steel plate, pine wood board and iron plate coated with green ocean self-cleaning antifouling coating only increased by 0.3 grams, 0.59 grams and 0.48 grams respectively ( Fig.13 ). These results show that the Green Ocean self-cleaning antifouling coating has excellent antifouling performance and can effectively inhibit the adhesion of fouling substances and slow down corrosion.

Claims

1. A photocatalyst, characterized in that: The photocatalyst is Zn3Fe2Ti 30 C3N6O 56 , its crystal form is anatase, and the lattice spacing is 3.63 Å; Tetrabutyl titanate is slowly poured into anhydrous ethanol and stirred to obtain solution A; anhydrous ethanol, acetylacetone and water are mixed in a certain proportion and stirred vigorously to obtain solution B; ferric chloride hexahydrate, urea and anhydrous zinc chloride are sequentially added to the above solution B and mixed evenly, and solution A is added dropwise thereto after mixing, and after the addition is completed, the solution is heated in a water bath to obtain yellow gel C; the yellow gel C is dried to obtain light yellow crystals D, which are ground to obtain light yellow powder; and the light yellow powder is calcined to obtain the photocatalyst Zn3Fe2Ti 30 C3N6O5; the dripping rate of solution A into solution B is controlled at 3-5 ml / min; the temperature of the water bath is 50-60 ℃ and the water bath time is 1-2 h; after the yellow gel C is formed, it is aged for 2-5 days; the drying temperature is 100-120 ℃ and the heating time is 20-24 h; the calcination temperature is 500-600 ℃ and the calcination time is 2-3 h.

2. A method for preparing the photocatalyst according to claim 1, characterized in that: Tetrabutyl titanate is slowly poured into anhydrous ethanol and stirred to obtain solution A; anhydrous ethanol, acetylacetone and water are mixed in a certain proportion and stirred vigorously to obtain solution B; ferric chloride hexahydrate, urea and anhydrous zinc chloride are sequentially added to the above solution B and mixed evenly, and solution A is added dropwise thereto after mixing, and after the addition is completed, the solution is heated in a water bath to obtain yellow gel C; the yellow gel C is dried to obtain light yellow crystals D, which are ground to obtain light yellow powder; and the light yellow powder is calcined to obtain the photocatalyst Zn3Fe2Ti 30 C3N6O 56 ; The dripping rate of solution A into solution B is controlled at 3-5 ml / min; the temperature of the water bath is 50-60°C and the water bath time is 1-2 h; after the yellow gel C is formed, it is aged for 2-5 days; the drying temperature is 100-120°C and the heating time is 20-24 h; the calcination temperature is 500-600°C and the calcination time is 2-3 h.

3. An application of the photocatalyst according to claim 1, characterized in that: The photocatalyst is used in preparing a green marine self-cleaning antifouling coating.

4. A green marine self-cleaning antifouling coating, characterized in that: The coating contains the photocatalyst according to claim 1, and the added amount thereof accounts for 1-1.5wt% of the coating mass.

5. The green marine self-cleaning antifouling coating according to claim 4 is characterized in that: The coating contains 95.0-97.0wt% of water-based resin, 0.8-1.0wt% of dispersant, 0.8-1.0wt% of leveling agent, 0.8-1.0wt% of defoamer, 1.0-1.0wt% of photocatalyst, and the balance is water, and the sum of the components is 100wt%.

6. The green marine self-cleaning antifouling paint according to claim 5 is characterized in that: The pH value of the water-based resin is 7.0±0.5, and the viscosity is 100.0-1000.0 cps.

7. Use of the green marine self-cleaning antifouling paint according to claim 4 as an antifouling coating for marine antifouling equipment.

Citation Information

Patent Citations

  • Nano marine anti-fouling coating

    CN102399486A

  • Titania photocatalytic compounds and methods of making the same

    CN104428063A

  • Preparation method of N, Fe and Zn-TiO2 / AC photocatalyst

    CN104907089A

  • Nano photocatalytic marine antifouling and anticorrosive paint and preparation method thereof

    CN114106610A